Chronic undernourishment in school-aged children: itineraries of nutritional neglect and official programs in indigenous communities of Guerrero, Mexico - Paul Hersch-Martínez; Julio Pisanty-Alatorre (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2016)
Through the analysis of different elements of the nutritional dynamics in a predominantly indigenous municipality in Guerrero, Mexico, we explore the relevance of the concept of itineraries of nutritional neglect in order to broaden the understanding of avoidable health damage. In the framework of a process of accompaniment of the Health Commission of the Regional Coordination of Community Authorities - Community Police, the following methodological strategies were applied throughout the year 2015: a) a review of official programs by means of the analysis of technical documents and interviews with health personnel; b) the compilation of local narratives from families of undernourished children through interviews and participatory observation; c) the somatometric measurement of 151 children in three elementary schools. We highlight the technical and cultural inadequacy of official nutrition programs and the existence of different scales (individual, familial, community, state, structural) and dimensions (economic, environmental, cultural, institutional, affective-emotional) of neglect, materialized in high rates of chronic undernourishment.